2007
DOI: 10.1016/j.neuroimage.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cortical abnormalities in epilepsy revealed by local EEG synchrony

Abstract: Abnormally strong functional linkage between cortical areas has been postulated to play a role in the pathogenesis of partial epilepsy. We explore the possibility that such linkages may be manifest in the interictal EEG apart from epileptiform disturbances or visually evident focal abnormalities. We analyzed samples of interictal intracranial EEG (ICEEG) recorded from subdural grids in nine patients with medically intractable partial epilepsy, measuring interelectrode synchrony using the mean phase coherence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
150
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 29 publications
18
150
0
Order By: Relevance
“…In most of these works the increase in the synchronization was found only during the seizure, while synchronization clusters, identified in [13], remain synchronized also during interictal periods. Similar stability of local hyper-synchronous regions was found also in [14]. In spite of demonstrated success, formulation of these methods involve some assumptions, that we would like to relax in our proposed approach, as it will be explained in the next Section.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In most of these works the increase in the synchronization was found only during the seizure, while synchronization clusters, identified in [13], remain synchronized also during interictal periods. Similar stability of local hyper-synchronous regions was found also in [14]. In spite of demonstrated success, formulation of these methods involve some assumptions, that we would like to relax in our proposed approach, as it will be explained in the next Section.…”
Section: Introductionmentioning
confidence: 70%
“…Previous observations involving different linear and non-linear measures [13,14,21,22,23] indicate that the values of the corresponding measures are altered over tumors and regions thought to be part of the epileptogenic zone. The regions of such a locally enhanced or suppressed activity are stable and have well defined edges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In epilepsy, abnormally synchronization rapidly spreads across a lot of cortical columns and even greater cortical areas via the dense network of short intracortical connections (Chagnac-Amitai and Connors, 1989) of about 1 to 5 millimeters length (Braitenberg, 1978). Abnormally synchronized EEG background activity does not respect anatomical borders and shows smooth gradients of the electric field as demonstrated by intracranial EEG (Schevon et al, 2007). Cross-modal validations and simulation studies showed that LORETA localization shows good correspondence with the reference imaging methods in these circumstances (Pascual-Marqui, 1999Oakes et al, 2004).…”
Section: Quantitative Eeg Analysesmentioning
confidence: 99%
“…An alternative way of thinking and research may start with realizing that all sorts of epilepsy are dynamic disorders. The epileptic brain may be characterized by abnormal network activities at large spatial scales (Bragin et al, 2000;Schevon et al, 2007;Spencer, 2002;Ponten et al, 2007;Horstmann et al, 2009). However, epilepsy is neither steady nor irreversible.…”
Section: Introductionmentioning
confidence: 99%